Pengaruh Terapi Slow Stroke Back Massage Terhadap Tekanan Darah Penderita Hipertensi Di Bangsal Pandawa RSU Diponegoro Dua Satu Klaten - Endang Setiowati; Anik Suwarni; Ni’mah Mufidah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Background: Hypertension is a serious, incurable health condition. Patients with high blood pressure require lifelong treatment to control their blood pressure and prevent significant increases. One non-pharmacological therapy for lowering blood pressure is a slow, stroke-back massage. Objectives: To determine the effect of slow stroke back massage on blood pressure in hypertensive patients at Diponegoro 21 Klaten General Hospital. Method: This study employed a pre-experimental design using a one-group pretest-posttest approach. The sample consisted of 60 respondents selected via purposive sampling. Data collection involved blood pressure measurement sheets and a sphygmomanometer. The slow stroke-back massage intervention was administered to respondents once and lasted approximately 10 minutes. Results: The Wilcoxon test for the 60 respondents yielded p = 0.001 (p < 0.05); thus, it can be concluded that slow stroke back massage therapy lowers blood pressure in hypertensive patients. Conclusion: Slow stroke back massage influences blood pressure in hypertensive patients at Diponegoro 21 Klaten General Hospital.